Forward genetic analysis of Toll-like receptor induced necroptosis and RIP1 kinase driven inflammation in wild-derived mice. - Schworer, Stephen. (2017)
Abstract: The innate immune system, including the Toll-like receptor family, recognizes invading pathogens and activates the immune response through the induction of cytokines and other antimicrobial factors. The outcomes of TLR ligation and signaling extend beyond activation of gene expression to include programmed cell death. When virus-encoded caspase inhibitors block caspase activity or when caspase expression in tissues is low, cells activate a necrotic cell death pathway through RIP1 and RIP3 known as necroptosis. In addition to established signaling pathways to trigger necroptosis such as TNF-R1, TLRs activate necroptosis when caspases are inhibited. Peritoneal macrophages from the wild-derived mouse strain MOLF are resistant to necroptosis when compared with the classical inbred strain C57BL/6. Forward genetic analysis using an N2 backcross panel identified two loci in which harboring a MOLF allele conferred resistance to TLR-induced necroptosis. One locus exhibited differential regulation of CYLD, a deubiquitinase that cleaves K63 and linear polyubiquitin chains from RIP1 and is known to promote necroptosis downstream of TNF-R1. CYLD was shown here to promote necroptosis driven by TRIF-dependent TLRs in the absence of TNF-R1. In MOLF peritoneal macrophages, TLR stimulation reduced Cyld mRNA expression and diminished protein levels. Decreased recruitment of RNA polymerase II to a promoter proximal site in MOLF Cyld suggested that a defect in promoter pausing or elongation may underlie CYLD downregulation. With low levels of CYLD, MOLF peritoneal macrophages are resistant to TLR-induced necroptosis when compared to B6, which express higher levels of CYLD. RIP1 kinase activity can also contribute to activation of gene transcription and cytokine production in the absence of caspase activity. While a scaffolding role for RIP1 is well documented for TNF-R1 and TRIF-mediated signaling pathways, RIP1 kinase activity augmented the induction of TNF and IFNβ after TLR4 ligation when caspases were inhibited by the pan-caspase inhibitor ZVAD. MOLF macrophages generated more cytokine mRNA through the RIP1 kinase dependent pathway than B6. MOLF but not B6 macrophages activated p38 in a RIP1 kinase-dependent manner through a mechanism involving IRAK2 and the activation of this arm of the MAPK pathway likely contributed to the more robust response of MOLF macrophages.; Thesis (Ph.D.)--Tufts University, 2016.; Submitted to the Dept. of Immunology.; Advisor: Alexander Poltorak.; Committee: Peter Brodeur, Stephen Bunnell, Miguel Stadecker, and Michelle Kelliher.; Keyword: Immunology.